Dampak Sindrom Digitalisasi Pada Cerpen Matahari Berkabel Oleh Oka Rusmini - Faomasi Faomasi; Ambarini Aningsari; Kiki Tugarma; Ayu Rosi; Cindy Cici; Putri Desata; Oka Rusmini; febri yudha anwar wibowo (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
The short story "Wired Sun" by Oka Rusmini highlights the issue of modern society's dependence on technology, especially the internet. Through Artha's story, this short story invites readers to reflect on our relationship with the digital world When Artha's internet broke, Artha felt very sad. He felt like he had lost something very important to him. This incident made Artha realize that the internet is an important thing, but not an absolute thing. Artha can live without the internet, but he has to try harder to get information and connect with other people. The short story "Wired Sun" gives the message that technology is a tool that can be used for good or evil. We must use technology wisely and responsibly. We also have to realize that technology is not everything